2019
DOI: 10.1186/s13104-019-4442-6
|View full text |Cite
|
Sign up to set email alerts
|

Birth outcomes of singleton term breech deliveries in Jimma University Medical Center, Southwest Ethiopia

Abstract: Objective Breech delivery is generally associated with higher perinatal morbidity and mortality than cephalic presentation. Hence describing the outcomes of singleton term breech deliveries in Jimma University Medical Center (JUMC), Southwest Ethiopia addresses in recommendation of improving perinatal outcomes and developing protocols in selecting eligible women. Results The incidence of singleton term breech delivery was 5.3%. Majority, (52.8%) of them had undergone em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 14 publications
2
5
0
Order By: Relevance
“…However, in our study, nearly half of breech presentations both in nulliparous and multiparous women were delivered vaginally (Table 3 ). This is similar to the 40% vaginal breech delivery observed in another teaching hospital in southwest Ethiopia [ 30 ]. A more liberal national and institutional protocols that allow assisted vaginal breech delivery in selected women can explain these observations [ 22 ].…”
Section: Discussionsupporting
confidence: 86%
“…However, in our study, nearly half of breech presentations both in nulliparous and multiparous women were delivered vaginally (Table 3 ). This is similar to the 40% vaginal breech delivery observed in another teaching hospital in southwest Ethiopia [ 30 ]. A more liberal national and institutional protocols that allow assisted vaginal breech delivery in selected women can explain these observations [ 22 ].…”
Section: Discussionsupporting
confidence: 86%
“…However, in our study, nearly half of breech presentations both in nulliparous and multiparous women were delivered vaginally ( Table 3). This is similar to the 40% vaginal breech delivery observed in another teaching hospital in southwest Ethiopia [27]. A more liberal national and institutional protocols that allow assisted vaginal breech delivery in selected women can explain these observations [21].…”
Section: Discussionsupporting
confidence: 78%
“…[6][7][8][9] However Assefa et al reported 5.3% as the incidence of breech delivery in their study. 5 The high incidence of breech delivery in our study might be because the hospital is a tertiary care center where the abnormal presentation cases are referred and also there is no practice of external cephalic version in our center.…”
Section: Discussionmentioning
confidence: 85%